Validation of a form to assess the self-care competence of the person with ventilation ostomy - Pereira,Brizida (2023)
Abstract Introduction: Self-care competence can improve health outcomes in people with a ventilation ostomy. The use of an instrument to assess the self-care competence of the person with an ostomy allows data collection to be organized and complete, facilitating the identification of nursing care needs. In Portugal there is no validated instrument that allows self-care competence of the person with a ventilation ostomy to be assessed. Objective: To assess the psychometric and clinimetric properties of the form to assess the self-care competence of the person with a ventilation ostomy. Methods: Methodological study in a non-probability sample of 195 participants. Results: The form presented high internal consistency values, over 0.90 in all domains. Inter-judge reliability, the Wilcoxon test, and the two-half test showed very similar values between assessors ​​in the evaluation performed. Regarding its validity, a positive inter-domain correlation and a good relationship between clinical variables were demonstrated. Conclusion: The instrument demonstrated good psychometric and clinimetric properties; however, further studies are needed to assess reliability and validity.